Family Education According to the Qur'an Surah At-Tahrim Verse 6 in Tafsir Imam Al Qurtubi - Primajaya Sembiring; Nurhasanah Nurhasanah (Indonesian Journal Education, 2025)
This study investigates the concept of family education contained in Surah At-Tahrim verse 6 through the interpretation of Imam Al-Qurtubi. The Qur’an positions itself not only as a theological guide but also as a comprehensive framework for human behavior, including educational practices within the family. Using a qualitative library research approach, this study examines primary sources in the form of Qur’anic texts and classical tafsir, supported by secondary literature from scholarly journals and previous studies. Data were analyzed descriptively by identifying educational values embedded in the verse. The results reveal that Surah At-Tahrim verse 6 emphasizes the believer’s responsibility to protect and guide the family from moral and spiritual destruction. This responsibility is manifested through self-education, emulating the noble character of the Prophet Muhammad, understanding the consequences of neglecting divine commands, and embodying the discipline demonstrated by the angels. These elements construct a holistic educational framework where the family becomes the earliest and most strategic environment for shaping religious character and moral resilience. Thus, Islamic family education is not merely an ethical recommendation, but a divine mandate with transformative implications for individual and communal well-being.